Arquitectura e Arqueologia: as Transformações da Paisagem - Mariana da Costa Oliveira Teixeira de Melo (2019)
This dissertation looks at how archaeological heritage forms part of the urban context, by studying the different ways in which one can achieve better protection and rehabilitation of archaeological sites. It aims at uncovering the dynamics between the past, the present and the future of the cultural heritage. In a nutshell, it discusses how to give a future to the past. Understanding the evolution of contemporary cities entails an in-depth analysis of the ruins and its interaction with the city context both now and in the future. The urban morphology is generally conditioned in the presence of archeological heritage. However, constant urban evolution tends to occur irrespective of the existence of the patrimony, which in turn leads the latter to become disproved of character and identity. For this reason, the proposed approach of this dissertation uses the ephemeral or transitory project concept to recoup the city's relationship with the archaeological heritage. Throughout this work, Ephemeral Architecture is viewed as paving the way to assess historical and cultural patrimony. Thus, both a theoretical and practical work are developed with the purpose of contributing to the on-going research in the field of architecture and archaeology.